2001
DOI: 10.1038/sj.onc.1204903
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory-type responses after exposure to ionizing radiation in vivo: a mechanism for radiation-induced bystander effects?

Abstract: Haemopoietic tissues exposed to ionizing radiation are shown to exhibit increased macrophage activation, de®ned by ultrastructural characteristics and increased lysosomal and nitric oxide synthase enzyme activities. Macrophage activation post-irradiation was also associated with enhanced respiratory burst activities and an unexpected neutrophil in®ltration. Examination of p53-null mice demonstrated that macrophage activation and neutrophil in®ltration were not direct e ects of irradiation, but were a consequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
216
0
3

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 346 publications
(233 citation statements)
references
References 43 publications
14
216
0
3
Order By: Relevance
“…Transient neutrophil infiltration and MIP-2 mRNA expression in the thymus have been observed after X-ray irradiation-induced apoptosis of thymic cells. 29 Lorimore et al 30 have shown that irradiation-induced apoptosis can stimulate proinflammatory responses by splenic macrophages, apparently by directing the ingestion of intact apoptotic cells. Consistent with the neutrophil infiltration observed in this work, there are reports that dying cells can trigger rapid release from macrophages of the neutrophil chemoattractant IL-8 (CXCL8) 31 and Fas ligand (CD95L).…”
Section: Discussionmentioning
confidence: 99%
“…Transient neutrophil infiltration and MIP-2 mRNA expression in the thymus have been observed after X-ray irradiation-induced apoptosis of thymic cells. 29 Lorimore et al 30 have shown that irradiation-induced apoptosis can stimulate proinflammatory responses by splenic macrophages, apparently by directing the ingestion of intact apoptotic cells. Consistent with the neutrophil infiltration observed in this work, there are reports that dying cells can trigger rapid release from macrophages of the neutrophil chemoattractant IL-8 (CXCL8) 31 and Fas ligand (CD95L).…”
Section: Discussionmentioning
confidence: 99%
“…75,79 These discrepancies may be explained by the activation or differentiation state of macrophages (discussed above), the source and activation state of target cells, the type of cell death stimuli, and the presence of TLR ligands resulting in differential recognition mechanisms and immunological consequences. Some bridging molecules, such as surfactant proteins A and D, have a dual function depending on binding orientation and on the receptor system that is triggered.…”
Section: Immunological Effects Of Dying Cell Clearancementioning
confidence: 99%
“…Lorimore and Wright (2003) have pointed out that intercellular signaling, production of cytokines and free radicals are features of inflammatory responses and have the potential for both bystander-mediated and persistent damage. Furthermore, they have in vivo evidence for inflammatory-type responses occurring in mice after irradiation (Lorimore et al, 2001). A hypothetical model unifying these features to explain dynamic radiation-induced genomic instability is proposed in Figure 6.…”
Section: Implications Of Nontargeted Effectsmentioning
confidence: 99%